2018
DOI: 10.1371/journal.pone.0193220
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic genetic diversity in the mottled rabbitfish Siganus fuscescens with mitochondrial introgression at a contact zone in the South China Sea

Abstract: The taxonomy of the mottled rabbitfish Siganus fuscescens species complex has long been challenging. In this study, we analyzed microsatellite genotypes, mitochondrial lineages, and morphometric data from 373 S. fuscescens individuals sampled from the northern Philippines and Hong Kong (South China Sea, Philippine Sea and Sulu Sea basins), to examine putative species boundaries in samples comprising three co-occurring mitochondrial lineages previously reported to characterize S. fuscescens (Clade A and Clade B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Those potentially result from introgressive hybridization and/or overlapping morphological characters. Several cases were expected as mitochondrial introgression was previously reported for Siganus based on a comprehensive assessment of genetic diversity at mitochondrial and nuclear markers (Kuriiwa, Hanzawa, Yoshino, Kimura, & Nishida, ; Ravago‐Gotanco, Cruz, Josefa Pante, & Borsa, ). In such cases that constitute a limit where sister‐species co‐occur and hybridize (Ravago‐Gotanco et al, ), mitochondrial markers will inflate the number of false positives (i.e .…”
Section: Discussionmentioning
confidence: 76%
“…Those potentially result from introgressive hybridization and/or overlapping morphological characters. Several cases were expected as mitochondrial introgression was previously reported for Siganus based on a comprehensive assessment of genetic diversity at mitochondrial and nuclear markers (Kuriiwa, Hanzawa, Yoshino, Kimura, & Nishida, ; Ravago‐Gotanco, Cruz, Josefa Pante, & Borsa, ). In such cases that constitute a limit where sister‐species co‐occur and hybridize (Ravago‐Gotanco et al, ), mitochondrial markers will inflate the number of false positives (i.e .…”
Section: Discussionmentioning
confidence: 76%
“…We revealed a steep change in haplotype frequency or an almost complete lack of shared genetic variation between the eastern and the western coasts of the SCS for six species of coastal fishes. Previous studies also reported a similar east‐west population break within the SCS for several species, including marine vertebrates and invertebrates [ Scomberomorus commerson (Fauvelot & Borsa, 2011); Hippocampus trimaculatus (Lourie et al, 2005); Ocypode ceratophthalmus (Ma, Chow, et al, 2018); Plectropomus leopardus (Ma, Van Herwerden, et al, 2018); Siganus fuscescens (Ravago‐Gotanco et al, 2018)]. Therefore, we newly recognize the east‐west population break within the SCS as the prevailing pattern for diverse marine organisms.…”
Section: Discussionmentioning
confidence: 61%
“…Rabbitfish (Siganidae) comprise 29 nominal extant species that are confined to a single genus, Siganus [ 1 , 2 , 3 ]. These coral reef fish are widely distributed across the Indo-West Pacific region and inhabit a variety of habitat types, ranging from estuaries, mangroves, and seaweed mats to the reef front and reef flat [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, intermediate body markings have been observed in some sister species that are distributed parapatrically in the Indo-West Pacific region. This suggests that introgressive hybridization may have occurred in the past, further affecting the taxonomic identification of siganids [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%